Cell-permeable mitochondrial ubiquinol–cytochrome c reductase binding protein induces angiogenesis in vitro and in vivo. Issue 1 (28th September 2015) - Chang, Junghwa; Jung, Hye Jin; Park, Hyun-Ji; Cho, Seung-Woo; Lee, Sang-Kyou; Kwon, Ho Jeong
Highlights: A novel PTD-UQCRB fusion protein was generated to allow the intracellular delivery of UQCRB. PTD-UQCRB localized to the mitochondria and induced mROS without cytotoxicity. Elevated mROS was sufficient to stabilize HIF-1α, resulting in downstream VEGF expression and angiogenesis in vitro . PTD-UQCRB efficiently enhanced angiogenesis and cutaneous wound healing in vivo . This study indicates that UQCRB engages in angiogenesis and that the novel PTD-UQCRB can be used as a pro-angiogenic agent. Abstract: Ubiquinol–cytochrome c reductase binding protein (UQCRB), a component of the mitochondrial complex III, has been recently implicated in angiogenesis. Targeting mitochondria to balance vascular homeostasis has been widely recognized. However, the effect of UQCRB replenishment by direct delivery remains unknown. To explore the biological function of UQCRB in angiogenesis, a novel protein transduction domain (PTD)-conjugated UQCRB fusion protein was generated. PTD-UQCRB localized to mitochondria as does endogenous UQCRB. Treatment with PTD-UQCRB generated mitochondrial reactive oxygen species (mROS) without cytotoxicity, following hypoxia inducible factor-1α (HIF-1α) stabilization and downstream vascular endothelial growth factor (VEGF) expression. Accordingly, PTD-UQCRB induced angiogenesis in vitro and PTD-UQCRB pro-angiogenic activity was further validated in matrigel plug assay and in cutaneous wound-healing mouse models in vivo . Together, these results demonstrate that UQCRB plays a role in angiogenesis and the developed cell-permeable PTD-UQCRB can be utilized as a pro-angiogenic agent.